Kajian Komparatif Sebelum Dan Pasca Launching Samsat Keliling Dan Samsat Corner Mall Terhadap Penerimaan Pajak Kendaraan Bermotor Di Provinsi Sumatera Selatan - Iwan Efriandy; Meita Rahmawati; Efva Octavina Donata (Jurnal Reformasi Administrasi : Jurnal Ilmiah untuk Mewujudkan Masyarakat Madani, 2020)
The South Sumatera Government wants to achieve the targets set in the Local Own-source Revenue (LOR), of which 40 percent comes from the motor vehicle tax and motor vehicle transfer fees. However, the LOR revenue target through vehicle tax and motor vehicle transfer fees set in 2016 only reached around 50 to 60 percent. In an effort to improve services that get closer to the community and increase the collection of vehicle tax in order to achieve the LOR targets in South Sumatera Province, the Provincial Government has launched a special mobile One-stop Administration Services Office (SAMSAT) in 21 Regional Technical Implementation Unit (UPTD) SAMSAT in 17 districts/cities and SAMSAT corner mall which is in 4 malls in Palembang city.The study aims to examine and analyze whether there are significant differences before and after the launching of mobile One-Stop Administration Service Office and SAMSAT corner mall on Vehicle Tax Revenue of South Sumatra Province